Preparation and properties of physically plasticized chitosan films - Al-Lami, Hadi Salman; Mutasher , Sara Hikmet (European Journal of Chemistry, 2025)
Food packaging prevents conditions that can reduce food quality and shelf life. This leads to environmental pollution because it does not degrade naturally. The food packaging industry is increasingly adopting biodegradable polymer films as an alternative to plastic packaging. They are receiving great attention and are more suitable for food applications because they do not need to be eliminated as solid waste, which is why the industry has recently begun to pay more attention to food packaging films derived from natural chitosan polymers to replace traditional synthetic polymers. Shrimp cortex was used to extract the chitosan using the casting procedure; It was plasticized with different ratios of polyvinyl alcohol (PVC), namely 1:1, 1:2, 1:3, and 1:4 to create plasticized chitosan films from its solution in 2% acetic acid by casting technique. All films prepared were examined by infrared spectroscopy (FT-IR) and were found to be comparable to the original chitosan spectrum, indicating that the basic composition of the basic polymeric chitosan chains was not affected by the addition of various ratios of PVC plasticizer. Unlike unplasticized chitosan films. The results of the mechanical tensile strength measurements of plasticized chitosan films showed an improvement in tensile strength, % elongation at breakage, and a decrease in the Young modulus, which means that less rigid films were obtained, with an enhancement in their optical properties accompanying this by decreasing the opacity from 85 for unplasticized chitosan to about 3 for plasticized chitosan films. The addition of plasticizer to chitosan was also found to increase the solubility of prepared plasticized chitosan films in water and reached 100% for 1:3 chitosan:PVA in contrast to the unplasticized chitosan polymer, which is insoluble in water.